CURRENT TRENDS OF THE CRYPTOINDUSTRY DEVELOPMENT IN UKRAINE - RUZAKOVA, Olga; KOLOTII, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the modern crypto industry market, examines its role, significance, dynamics and possibilities of further application in our country. The history of the cryptocurrency concept is presented. The development path of the domestic cryptoindustry from complete non-recognition to attempts to regulate this sphere by law is illustrated. The advantages and disadvantages of cryptocurrency as a payment were studied, the trends of its development in Ukraine and in the whole world were considered. The research identified three main groups of digital currencies and assets: cryptocurrencies, stablecoins, and digital currencies of central banks. The first group includes traditional cryptocurrencies, that is, those that are not backed by other assets and have a decentralized register of owners (Bitcoin, , Ripple, Ethereum). The second group of digital currencies and assets includes stablecoins — cryptocurrencies backed by one asset or a basket of some assets. The third group includes digital currencies of central banks, which are currently issued in a limited way as part of pilot projects, or government-issued cryptocurrencies. An analysis of the cryptocurrency market was conducted; a conclusion about the positive dynamics of the use of cryptocurrency in our country was made. The dynamics of the ratio of the cryptocurrency market capitalization to the indicators of GDP are estimated. The impact of military events on the cryptoindustry development was studied. The contribution of the global crypto-community to Ukrainian charitable foundations was studied. The advantages of the latest technologies in the war conditions are indicated, in particular, the speed and efficiency of transaction processing, the absence of restrictions inherent in classical finance. The domestic and global experience of cryptocurrency regulation is analyzed. It is noted that it is necessary to develop further measures to regulate the cryptocurrency market in a legislative manner. It is proposed to create associations consisting of IT lawyers, cyber police and blockchain developers. This stimulates the emergence of new methods of combating terrorism and the development of a new legislative model. Possible directions of cryptocurrency development and prospects for their development are proposed.